Trial Conduct, Baseline Characteristics, and Symptom Burden of Patients in the ARISE Study - Daley, Charles L.; Chalmers, James D.; Flume, Patrick A.; Griffith, David E.; Hasegawa, Naoki; Morimoto, Kozo; Winthrop, Kevin L.; Sheu, Chau-Chyun; Avsar, Korkut; Andrisani, Dario; Codecasa, Luigi Ruffo; Yuen, Dayton W.; et al. (Pulmonary therapy, 2025)
Introduction ARISE was a global clinical trial designed to generate evidence demonstrating the utility of the patient-reported outcome instruments Quality of Life–Bronchiectasis (QOL-B) [Respiratory Domain (RD) only] and Patient-Reported Outcomes Measurement Information System Short Form v1.0-Fatigue 7a (PROMIS F SF-7a) in patients with newly diagnosed or recurrent Mycobacterium avium complex lung disease (MACLD). Here, we describe trial conduct, patient characteristics, and patient-reported symptoms at baseline among patients enrolled in ARISE. Methods Adult patients with newly diagnosed or recurrent non-cavitary MACLD who had not initiated antibiotic treatment for their current MAC infection were enrolled; data including comorbidities and prior MACLD history were collected during screening. Symptom burden was assessed using QOL-B, PROMIS F SF-7a, and Functional Assessment of Chronic Illness Therapy (FACIT) questionnaires. Results Of 99 patients from 12 countries enrolled in ARISE, the median age was 69.0 years; most were white (80.8%) and female (77.8%). This was the first diagnosis of MACLD for 72.7% of patients. Patients frequently reported having a comorbid respiratory disorder: bronchiectasis (49.5%), asthma (21.2%), and chronic obstructive pulmonary disease (16.2%). At baseline, mean (± SD) and median QOL-B RD scores were 65.0 (± 15.3) and 66.7; PROMIS F SF-7a T-scores were 53.8 (± 8.2) and 55.1; and FACIT-Fatigue scores were 35.0 (± 9.6) and 37.0. Conclusions Patients in ARISE were representative of a real-world patient population with MACLD. Comorbid chronic respiratory diseases were common in patients with new or recurrent MACLD, and substantial disease burden at the time physicians initiated MACLD treatment was evidenced by impairment across measures of fatigue and QOL-B domains. ClinicalTrials.gov Identifier NCT04677543. Graphical Abstract Plain Language Summary People with a disease called Mycobacterium avium complex lung disease (MACLD) experience many symptoms, including cough, fatigue, and shortness of breath, which can impact their quality of life. It is not clear what symptoms people with new or repeating MACLD may have before they start antibiotic treatment for their disease. This publication describes the design of a study called ARISE, characteristics of people with MACLD who participated, and the symptoms they reported when they started the study. Overall, 99 people with a first, second, or third diagnosis of MACLD, who had not started taking antibiotics, participated in the study. People in the study were on average 69 years old and most were female (78%). This was the first diagnosis of MACLD for more than 70% of people who participated in ARISE. In addition to MACLD, many people also had other respiratory diseases, including bronchiectasis, asthma, and chronic obstructive pulmonary disease. At the start of the study, people completed three questionnaires that measured their symptoms, quality of life, and the severity and frequency of fatigue in their daily life. In these questionnaires, people with MACLD reported that, before starting treatment, they had a high burden of symptoms that impacted their daily lives and quality of life. They also reported more fatigue than people without MACLD. The results from this study were similar to those seen in people with MACLD from registries and other clinical studies. The results also showed that people with MACLD have a large symptom burden before starting treatment.